Cutting force models for Fe–Al-based coating processed by a compound NC machine tool. Issue 1 (July 2015) - Sun, Yewang; Zhang, Zhijing; Zhang, Jiaying; Jin, Xin; Xu, Binshi; Zhao, Gang
Abstract The arc-spraying Fe–Al-based coating cutting process is a spindle-tool-workpiece vibration system dependent upon the machine tool's dynamic performance, cutting tool vibration, the coarse coating surface and its thin cutting depth. To investigate the cutting force, this research indicates the coating cutting fundamental mechanics; furthermore, it represents two cutting steps and cutting force models in the machining process avoiding an analysis of the natural vibration parameters of the machine tool itself. In the first cutting step, there is a transient cutting force due to forced vibration of the rough surface; the second cutting step has a steady machining feature based on the first cutting surface and the reduced hardness of the inhomogeneous region. According to the different characteristics of each cutting step, this research presents dynamic cutting calculation models including cutting parameters, tool vibration and cutting depth effects in the first cutting step. A steady cutting model is based on three cutting parameters including cutting velocity, cutting feed and cutting depth. Piezoelectric force and acceleration sensors were used to obtain accurate experimental data. Then, response surface methodology (RSM) and the principle of least squares estimation of polynomial regression (PLSEPR) were applied to analyse the resultant cutting data. The results showed that cutting force calculation models were suitable for the coating machining.